Towards enhancing the compilation of Al-Hadith text in Malay - Bimba, A.; Ismail, M.A.; Idris, N.; Jaafar, S.; Mahmud, R. (2015)
The statement and conducts of Prophet Muhammad (SAW), was memorized, written down and later passed by his companions from one generation to another. Later, as the authenticity of the text became threatened, Islamic scholars from Muslim nations collected thousands of these narratives and distinguished the true wisdom from fabricated ones. However, statements are still attributed to the Prophet by individuals with no knowledge of al-Hadith. Currently, with the existence of the internet and the popularity of social media, the threat to the access and existence of fake al-Hadith is more likely than ever. Our first step to handling this challenge is to develop a tool that will enhance the process of compiling authentic al-Hadith from various sources. Due to the sensitive nature of al-Hadith text the tool must be reliable. To achieve this reliability a well-structured relational database with a user interface was designed and developed to store al-Hadith text in Malay Language. These development will enhance the compilation process, by ensuring data is stored appropriately. Subsequently, the tool will serve as a reference guide to the general public, who wish to verify the authenticity of al-Hadith in Malay text. Furthermore, it provides computer scientist with an opportunity to extract, analyze and perform inference on the data.